Large deviations for impulsive processes in the scheme of Poisson approximation - Samoilenko, I. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Asymptotic analysis of the large deviation problem for impulsive processes in the scheme of Poisson approximation is performed. Large deviations for impulsive processes in the scheme of Poisson approximation are defined by an exponential generator for a jump process with independent increments.